Dynamism in Dupuytren's contractures. (February 2015) - Rodrigues, J. N.; Zhang, W.; Scammell, B. E.; Davis, T. R. C.
Dynamism of Dupuytren's contractures may occur if a contracture crosses over both the metacarpophalangeal (MCPJ) and proximal interphalangeal (PIPJ) joints of one finger. In this situation the extension deficit at one joint can be influenced by the position of the other. This may affect clinical measurements and introduce errors and bias into research using angular deformity as an endpoint. This study reports the dynamism encountered when measuring passive joint extension deficits in pre-operative contractures. Eighty-five digits with a contracture affecting the PIPJ or MCPJ and PIPJ on 72 hands from 70 patients were studied. Seventy-six digits showed dynamism at either the MCPJ or PIPJ (89%). Seventy-four showed dynamism at the PIPJ (87%). The mean dynamism observed was 6° at the MCPJ and 14° at the PIPJ. Previous Dupuytren's surgery to the finger did not influence the amount of dynamism seen. Dynamism is common and may be a source of error or bias in trials of Dupuytren's disease treatment. Level of evidence: III